Guanidine sulfate-assisted synthesis of hexagonal WO3 nanoparticles with enhanced adsorption properties. Issue 16 (24th March 2015) - Mu, Wanjun; Li, Mei; Li, Xingliang; Ma, Zongping; Zhang, Rui; Yu, Qianhong; Lv, Kai; Xie, Xiang; He, Jiaheng; Wei, Hongyuan; Jian, Yuan
Abstract : The hexagonal WO3 nanowires prepared with the assistance of C2 H10 N·H2 SO4 possess a large specific surface area and numerous adsorption functional groups, consequently improving the Sr 2+ adsorption capacity considerably. Abstract : Large surface area hexagonal phase WO3 (h-WO3 ) nanowires were synthesized by a hydrothermal route with the assistance of C2 H12 N6 O4 S. They were characterized by XRD, SEM, TEM, BET, FT-IR and XPS. It is shown that C2 H12 N6 O4 S not only acts as a stabilizer to facilitate the generation of a metastable hexagonal phase, but also functions as a structure directing agent to assist the construction of nanowires. The obtained h-WO3 possesses a large specific surface area and numerous adsorption functional groups such as –OH groups. These characteristics result in an excellent adsorption performance for the removal of strontium from acidic aqueous solutions. A maximum adsorption capacity of 52.93 mg g −1 was achieved on the h-WO3 prepared in the presence of C2 H12 N6 O4 S. This value is almost two times higher than that of bare h-WO3 (no C2 H12 N6 O4 S). The effects of pH, contact time, initial Sr 2+ concentration and ion strength on Sr 2+ removal from the solution by h-WO3 were systematically investigated. The adsorption mechanism involving the combination of electrostatic attraction and ion exchange for the adsorption of Sr 2+ is proposed. Based on our results, h-WO3 with high adsorption capacity and good surface characteristics exhibits great potential for the removal of Sr 2+ from radioactive wastewater.